SPATIAL ARRANGEMENTS FOR DRY BEAN AT CONVENTIONAL CROP SYSTEM - SCHAMNE, José Antonio; RONZELLI JÚNIOR, Pedro; DAROS, Edelclaiton; KOEHLER, Henrique Soares (Scientia Agraria, 2001)
A field trial was carried out at Cangüiri Experimental Station of The Universidade Federal do Paraná from January, 13th till April, 18th 2000. The objective was to determine the most adequated spatial arrangement for dry beans in conventional crop system. The variety used was 'FT Bionobre'. The experimental design was a randomized complete block, with four treatments (0.30 m, 0.40 m, 0.50 m and 0.60 m row width) arranged in strips and six replications. There were evaluated: yield, grain weight, seeds per pod and apparent harvest index. In order to evaluate the morphological characteristics, a randomized complete block for width row, with developmental stages V4, R6, R7, R8 and R9 split plot on it, was used. Plots were formed by ten rows with 5.0 m length. Populations were standardized by thinning in the four width rows, in which remained about 8.1; 10.8; 13.5; and 16.2 plants.m-1. Tendency of leaf area increasing and apparent harvest index decreasing was observed when row width was increased. Greater leaf area associated with low water availability can have contributed to diminish the yield. Yield in 0.30 m row width was greater than the yield in 0.60 m.